REVIEWS - Lambert, W. G. (Journal of Semitic studies, 2003)
Mari and the Bible (Studies in the History and Culture of the Ancient Near East 12) AbrahamMalamat . Brill, Leiden , 1998. Pp. viii + 270 Price: €83.00/$97.00 . ISBN: 3-447-04318-0.